New data on early pottery traditions in South America: the San Pedro complex, Ecuador. (12th June 2019) - Kanomata, Yoshitaka; Marcos, Jorge; Popov, Alexander; Lazin, Boris; Tabarev, Andrey
Abstract: Abstract : Sherds of the San Pedro pottery complex found in situ in association with new radiocarbon dates at the Real Alto site provide new insights into the origin of pottery technology in South America and cultural diversity during the Early Formative period on the coast of Ecuador.